Sociological Diagnostics of the Image of a “hero” as an Object of Social Construction in the Ideology of Youth, during a Special Military Operation - A. S. Kurapova; S. V. Kurapov; A. B. Ilchenko (Дискурс)
Introduction. The article examines the application of the concept of social construction to the formation of the image of a “hero” among students and its sociodynamics during a special military operation. Conscripts and Cossack youth were taken for comparative analysis. The importance of the influence of images of “heroes” that meet certain requirements in the conditions of “hybrid war” is noted.Methodology and sources. The main approaches to social construction from the position of forming the image of a “hero” are presented (A. Schutz, P. Berger, T. Lukman, G. Bloomer, K. Popper, M. Spector, J. Kitseuse, W. Lippman). The factors influencing the formation of the image of the “hero” and the procedures of social construction are described. The interrelation of the constructed image of the "hero" and the result of its functioning in the social environment is shown. The influence of mass media and social networks on the formation of the image of a “hero” is substantiated, the concept of a social construct is described: representations of youth – value choice – result. The research data of the authors of the article on the value orientations of young people are presented.Results and discussion. The results of sociological diagnostics of the image of the “hero” in the dynamics of 2022–2023 are presented. This diagnosis was carried out among students in St. Petersburg and Moscow, as well as among a group of young people to whom targeted social technologies were applied (specifically, conscripts and Cossack youth).Conclusion. In the second year of the special military operation, there was a transformation of the image of a ‘hero’ for all groups of young people. The students were influenced by the social construction of “soft power”. For example, changing the broadcast content on the Internet, introducing special lessons of courage and “Talking about important things”. However, the standard of the “warrior hero” remains at the level of the Great Patriotic War, which indicates insufficient historical immersion of the transmitted information, and, at the same time, insufficient actualization of modern warrior heroes. The results are somewhat different for young people focused on the military sphere (on the example of Cossack youth). By purposeful social construction (political information, direct communication with the participants of a special military operation, studying the history of Russia, etc.), the image of the “hero” turns out to be stronger and more reliable.